2012
DOI: 10.1002/anie.201202044
|View full text |Cite
|
Sign up to set email alerts
|

Fantastic Voyage: Designing Self‐Powered Nanorobots

Abstract: The use of swarms of nanobots to perform seemingly miraculous tasks is a common trope in the annals of science fiction.1 Although several of these remarkable feats are still very much in the realm of fiction, scientists have recently overcome many of the physical challenges associated with operating on the small scale and have generated the first generation of autonomous self-powered nanomotors and pumps. The motors can be directed by chemical and light gradients, pick up and deliver cargo, and exhibit collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
253
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(260 citation statements)
references
References 137 publications
(164 reference statements)
4
253
0
3
Order By: Relevance
“…Beyond the limitless imagination of writers, this points towards a challenging question for the scientific community: how can we design populations of artificial microagents capable of moving autonomously in a controlled fashion while performing complex tasks? Recently, this question has fuelled a great effort towards the fabrication and the development of the first generation of synthetic micro-and nano-robots [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the limitless imagination of writers, this points towards a challenging question for the scientific community: how can we design populations of artificial microagents capable of moving autonomously in a controlled fashion while performing complex tasks? Recently, this question has fuelled a great effort towards the fabrication and the development of the first generation of synthetic micro-and nano-robots [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by early observations of Martin and coworkers who reported that GOx nanotubes -prepared by a similar protocol -are able to catalyze the oxidation of glucose. 31 Most favourable results were observed using 10 mM glucose, 0.3 mM AuCl 4 À and following an initial 30 min incubation time. No apparent patterning was noticeable using incubation times shorter than 15 min or using glucose concentrations lower than 1 mM.…”
mentioning
confidence: 98%
“…Previously we demonstrated that such magnetically powered nanowire motors, containing a exible silver joint, can swim efficiently under an external rotating magnetic eld. 27 As illustrated in Scheme 1 our new surface 'writing' concept relies on the connement of GOx onto the Au end of a exible Au/ Ag ex /Ni magnetic 5.5 mm long nanowire motor for localized biometallization through a H 2 O 2 -mediated deposition of helical Au microwires in the presence of glucose and AuCl 4 À ions. The enzyme connement onto the end of the Au segment was accomplished by covalent immobilization using carbodiimide/succinimide onto a carboxylic acid terminated alkanethiol thiolated self-assembled monolayer (SAM) (see Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations